Vaccination programs for pregnant women in Europe, 2021. Issue 41 (1st October 2021) - Maltezou, Helena C.; Effraimidou, Evgnosia; Cassimos, Dimitrios C.; Medic, Snezana; Topalidou, Maria; Konstantinidis, Theocharis; Theodoridou, Maria; Rodolakis, Alexandros
Abstract: Vaccination during pregnancy is increasingly adopted worldwide in order to protect the mother and her offspring. We studied the current vaccination programs specifically for pregnant women in 42 European countries. Vaccination programs for pregnant women are in place in 37 countries, as follows: influenza (36 countries), pertussis (28), hepatitis B (12), tetanus (10), pneumococcal disease (10), meningococcal disease (10), rabies (8), tick-borne encephalitis (6), hepatitis A (5), poliomyelitis (4), diphtheria (3), Haemophilus influenzae (2), and human papilloma virus (1). Recommendations for vaccination against influenza and pertussis concern almost exclusively pregnant women regardless of high-risk conditions, however differences between vaccination recommendations are noted in terms of timing. Vaccinations against hepatitis B, hepatitis A, pneumococcal disease, meningococcal disease, poliomyelitis, H. influenzae, rabies, and tick-born encephalitis mainly concern pregnant women at high-risk for exposure or serious illness and post-exposure vaccinations. Overall, five European countries have no vaccination recommendations specifically for pregnant women. In conclusion, there are significant differences in vaccination programs for pregnant women in Europe. Vaccination programs for pregnant women should expand in order to protect maternal and infant health. A consensus-based vaccination program is needed.